Performance Evaluation of Certified Teachers Using the Charlotte Danielson Model Approach - Hendra Sahputra Batubara; Agung Kurniawan; Indra Bulan; Afif Rahman Riyanda; Ambiyar Ambiyar; Fahmi Rizal (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to assess the performance of teachers who have passed certification in High School/Vocational School in North Sumatra and Lampung in terms of: (1) learning planning and preparation, (2) Class Management (3) Learning Aspects. and (4) Professional Responsibilities. This research is an evaluative research using the Charlotte Danielson Model. The subjects of this study were ten teachers who had passed the certification. The research was conducted on 10 teachers with a quantitative approach. The quantitative approach uses data collection techniques in the form of questionnaires and instruments. The results of this study are: (1) the performance of certified teachers is in the Good category. with a large percentage of 82.92%, (2) the performance of certified teachers from the Classroom Management aspect is in the Good category, (3) the performance of certified teachers in interacting with students during learning is in the Good category, and (4) the performance of certified teachers shows the ability professional responsibilities as a teacher are categorized as good. However, the results are still not entirely good, because from the aspect of professional responsibility assessed, this aspect gets the lowest percentage, which is 78.75%. Of course, the professional responsibilities of certified teachers in High School/Vocational School in the Provinces of North Sumatra and Lampung need to be increased again.